Pengembangan Wisata Bahari di Pulau Raas dalam Rangka Menggerakkan Perekonomian Lokal - Icha Rizky Rifatussoliha; Khusairi Abdy; Muhfiatun Muhfiatun; Abdul Wahid (Journal of Dedicators Community, 2019)
This community service aims to improve the potential of the archipelago, especially from the marine tourism sector. Against the background of not optimal management of tourism potential in the District of Raas which is an archipelago and has potential places to become a tourist. Development of Marine Tourism on Raas Island in Order to Mobilize the Local Economy. The process of developing marine tourism is done by mapping, observation, community empowerment and literature study. Based on the results of mapping and observation shows that there are 3 beaches that have attraction and are very potential, just need to be developed again and also managed properly. The three beaches also have different characteristics so that if the tours offered are not monotonous. The conclusion of the process of developing marine tourism is the need for awareness of the local community and also the cooperation of various parties and also agencies to work together to develop and build supporting facilities that can support these three potential beaches into a marine tourism that is not only a power pull Raas District alone, but also can be a pillar of the people's economy